2011
DOI: 10.1177/0730888410397924
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing Management Citizenship Behavior and Testing Its Impact on Employee Commitment, Satisfaction, and Mental Health

Abstract: How can employers create conditions that foster satisfied, psychologically healthy, and committed employees? To answer that, the authors build on Hodson’s concept of management citizenship behavior (MCB). The authors incorporate managers’ ethical and family-supportive behaviors as essential components of MCB. The authors operationalize these constructs using data from the National Survey of the Changing Workforce. The study results demonstrate strong positive effects of MCB on employees’ commitment, job satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 56 publications
1
54
0
Order By: Relevance
“…Employees characterized workplace transformation as beneficial because they became better workers, and there were more opportunities. They framed changes as fair and just, which, in turn, maintained loyalty, pride, and commitment (Hodson, 2002;Rubin & Brody, 2011;Swanberg et al, 2005). Rather than eroding the employeremployee contract, the findings suggested that the new strategies did not disrupt the family-supportive setting, leading employees to interpret the actions as reinforcing trust and reciprocity.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Employees characterized workplace transformation as beneficial because they became better workers, and there were more opportunities. They framed changes as fair and just, which, in turn, maintained loyalty, pride, and commitment (Hodson, 2002;Rubin & Brody, 2011;Swanberg et al, 2005). Rather than eroding the employeremployee contract, the findings suggested that the new strategies did not disrupt the family-supportive setting, leading employees to interpret the actions as reinforcing trust and reciprocity.…”
Section: Discussionmentioning
confidence: 81%
“…Hodson (2002) argues that managerial behaviors that create employer-employee trust, reciprocity, and legitimacy can encourage employees to exhibit pride, loyalty, and give more at work. Whereas perceived poor managerial behaviors are associated with increased worker conflict (Plankey Videla, 2012) and work group infighting (Hodson, 2002), evidence shows higher levels of commitment when employees report positive managerial ethics (Rubin & Brody, 2011). Positive managerial actions also include perceived supervisor support and work-family policies (Allen, 2001;Blair-Loy & Wharton, 2004).…”
Section: Organizational Commitmentmentioning
confidence: 96%
“…Furthermore, supervisor and coworker instrumental and emotional support are associated with greater job satisfaction (Chou & Robert, 2008), a variable that is inversely related to psychological difficulties (Mark & Smith, 2012). Additionally, investigations of workplace support aimed at promoting a healthy work-life balance have demonstrated positive effects on workers' ability to cope with job pressure (Abendroth & Dulk, 2011) and employees' mental well-being ( Jang, Park, & Zippay, 2011;Rubin & Brody, 2011). Thus, deliberately modifying task and organizational characteristics results in the enhanced psychological functioning of workers and serves to protect against the development of psychopathology, a significant risk factor for suicidal behavior.…”
Section: Creating Workplace Barriers To Suicidementioning
confidence: 95%
“…Research in the sociology of work suggests that management behaviors are paramount in eliciting positive employee attitudes, efforts, and commitment, particularly as work becomes further degraded and precarious under shareholder capitalism (Crowley ; Crowley and Hodson ; Davis ; Kalleberg ; Rubin and Brody ). The more that managers are forced to attend to shareholder interest above employee well‐being, and the more they face globalized pressures to heighten productivity at the lowest possible cost, the less likely these beneficial managerial behaviors are to prevail (Crowley ; Crowley and Hodson ; Davis ; Kalleberg ).…”
Section: Introductionmentioning
confidence: 99%
“…The more that managers are forced to attend to shareholder interest above employee well‐being, and the more they face globalized pressures to heighten productivity at the lowest possible cost, the less likely these beneficial managerial behaviors are to prevail (Crowley ; Crowley and Hodson ; Davis ; Kalleberg ). This is ironic, however, because managerial citizenship is most likely to promote employee productivity (Crowley ; Crowley and Hodson ; Hodson ; Rubin and Brody ). The question at stake is thus how managerial citizenship behaviors can enhance employee well‐being and productivity without great extra cost to employers (Crowley ; Crowley and Hodson ; Rubin and Brody ).…”
Section: Introductionmentioning
confidence: 99%